Catalytic intramolecular hydroamination of aminoallenes using titanium complexes of chiral, tridentate, dianionic imine-diol ligands. Issue 26 (19th February 2019) - Sha, Fanrui; Mitchell, Benjamin S.; Ye, Christopher Z.; Abelson, Chase S.; Reinheimer, Eric W.; LeMagueres, Pierre; Ferrara, Joseph D.; Takase, Michael K.; Johnson, Adam R.
Abstract : Earth abundant and non-toxic titanium catalysts supported by readily prepared chiral ligands catalyze hydroamination of aminoallenes that lack-protecting groups. Abstract : Alkylation ofd - orl -phenylalanine or valine alkyl esters was carried out using methyl or phenyl Grignard reagents. Subsequent condensation with salicylaldehyde, 3, 5-di- tert -butylsalicylaldehyde, or 5-fluorosalicylaldehyde formed tridentate, X2 L type, Schiff base ligands. Chiral shift NMR confirmed retention of stereochemistry during synthesis. X-ray crystal structures of four of the ligands show either inter- or intramolecular hydrogen bonding interactions. The ligands coordinate to the titanium reagents Ti(NMe2 )4 or TiCl(NMe2 )3 by protonolysis and displacement of two equivalents of HNMe2 . The crystal structure of one example of Ti(X2 L)Cl(NMe2 ) was determined and the complex has a distorted square pyramidal geometry with an axial NMe2 ligand. The bis-dimethylamide complexes are active catalysts for the ring closing hydroamination of di- and trisubstituted aminoallenes. The reaction of hepta-4, 5-dienylamine at 135 °C with 5 mol% catalyst gives a mixture of 6-ethyl-2, 3, 4, 5-tetrahydropyridine (40–72%) and both Z - and E -2-propenyl-pyrrolidine (25–52%). The ring closing reaction of 6-methyl-hepta-4, 5-dienylamine at 135 °C with 5 mol% catalyst gives exclusively 2-(2-methyl-propenyl)-pyrrolidine. The pyrrolidine products are obtained with enantiomeric excesses up to 17%.